(untitled) (Minerva, 2019)
The Povest vremmenykh let is supposed the most ancient Russian chronicle. Both its sources and ideology reveal the debt to Greek chronicles, but it is really original as well. An approach to the first part of the chronicle, a kind of “introduction” to universal history from the creation of the world to the very Russian history, will show some important aspects of the medieval historiographical genres, the cultural and political relations between the Kievan Rus and the Byzantine Empire and the formation of Russian identity.